PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA PADA MATA PELAJARAN IPA KELAS VIII.2 SMPN 21 PEKANBARU - Nadia Nadia; Evi Suryawati; Marinani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to improve students' scientific literacy skills through the application of the 5E Learning Cycle model in class VIII.2 science subjects in Pekanbaru 21 Junior High School. This research is a Classroom Action Research (CAR) conducted in two cycles. The subject of this study was class VIII.2 of SMPN 21 Pekanbaru in 2018/2019 academic year, amounting to 41 people consisting of 20 male students and 21 female students. The parameters measured in this study are scientific literacy skills, cognitive aspects, skills and attitudes of students. The research instruments used were syllabus, lesson plans, student worksheets, student skills observation sheets, student attitude observation sheets, knowledge assessment sheets (post test) and daily test sheets. The results showed that the average value of students' scientific literacy skills in the first cycle of learning was 78.14 (C) and in the second cycle the average value of scientific literacy skills increased to 86.48 (B). The average absorption of students in the first cycle was 68.32 (C) and increased in the second cycle to 84.07 (B). The completeness in learning cycle I was 46.30% (D) and the second cycle had reached 85.36% (B). The average value of attitudes of students in learning cycle I is 77.43 (C) and increases in the second cycle to 89.65 (B). The average value of the skills of students in learning cycle I is 63.11 (D) and increases in cycle II to 84.01 (B). Based on the results of the study it can be concluded that the application of the 5E Learning Cycle model can improve students' scientific literacy skills in class VIII.2 science subjects in SMP Negeri 21 Pekanbaru.Keywords: 5E Learning Cycle, scientific literacy, science lessons